2021
DOI: 10.1017/s1368980021000719
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity, food skills, health literacy and food preparation activities among young Canadian adults: a cross-sectional analysis

Abstract: Objective: To assess associations between household food security status and indicators of food skills, health literacy, and home meal preparation, among young Canadian adults. Design: Cross-sectional data were analyzed using logistic regression and general linear models to assess associations between food security status and food skills, health literacy, and the proportion of meals prepared at home, by gender. Setting: Participants recruited from five Canadian cities (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
13
1
Order By: Relevance
“…This may relate to the relatively better dietary habits or better access to fresh water in this group. Lastly, in the current study, only a third of respondents reported consuming breakfast daily regardless of food security status, which is lower than in other studies of young people in Australia showing 92% consume breakfast daily 45 . However, a study by Pepetone et al 46 reported that young women in food‐insecure households reported preparing a lower proportion of breakfasts at home, which was related to financial precarity, rather than lack of food skills.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…This may relate to the relatively better dietary habits or better access to fresh water in this group. Lastly, in the current study, only a third of respondents reported consuming breakfast daily regardless of food security status, which is lower than in other studies of young people in Australia showing 92% consume breakfast daily 45 . However, a study by Pepetone et al 46 reported that young women in food‐insecure households reported preparing a lower proportion of breakfasts at home, which was related to financial precarity, rather than lack of food skills.…”
Section: Discussioncontrasting
confidence: 83%
“…Lastly, in the current study, only a third of respondents reported consuming breakfast daily regardless of food security status, which is lower than in other studies of young people in Australia showing 92% consume breakfast daily. 45 However, a study by Pepetone et al 46 reported that young women in foodinsecure households reported preparing a lower proportion of breakfasts at home, which was related to financial precarity, rather than lack of food skills. These findings suggest a need for interventions to substantially improve the dietary habits of young people attending youth mental health services, regardless of food security status.…”
Section: Discussionmentioning
confidence: 98%
“…A number of European countries have reported that low education, old age, and financial scarcity are commonly associated with low health literacy [ 28 , 29 ]. However, information on the relationship between sex and health literacy is still lacking, and the results of health literacy according to sex suggest otherwise [ 30 , 31 ]. Individuals with IFG need health and food information they can understand and use in order to maintain target blood glucose levels and properly manage their health [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diet cost has also been shown to mediate the pathway between income and diet quality [ 18 ]. Although individuals can experience financial difficulties across all socioeconomic groups, these problems have a larger influence on everyday food choices and eating practices of individuals with disadvantaged SEC [ 25 , 47 ].…”
Section: Discussionmentioning
confidence: 99%